Evolution of Fe-containing intermetallic phases and abnormal grain growth in 6063 aluminum alloy during homogenization - Kanokwan Uttarasak (2019)
© 2019 The Authors The 6063 aluminum billet alloy has been widely used as raw materials for aluminum extrusion profiles. A high-quality billet for good extrusion products is provided from a heat treatment process called homogenization. This process can give a homogeneous microstructure by reducing microsegregation and dissolving intermetallic phases. However, homogenization can create a very large grain size (abnormal grains) in 6063 aluminum billets. Fe content is one of the main factors that is strongly related to abnormal grain growth because Fe can form Fe-containing intermetallic phases in 6063 aluminum structure. The morphology and volume fraction of Fe-containing intermetallic phases are subjected to change during homogenization. These results relate to a decrease in the volume fraction of intermetallics, which corresponds to the Zener pinning pressure, grain boundary migration, and abnormal grain growth. Therefore, this study aims to understand the evolution of Fe-containing intermetallic phases on abnormal grain growth in 6063 aluminum billets during homogenization. Ex-situ characterization by energy dispersive spectrometer (EDS) and electron backscattered diffraction (EBSD) was performed on 6063 aluminum alloy to gain an in-depth understanding of abnormal grain growth.